Electrical and Thermal Behaviour of Crystalline Photovoltaic Solar Modules in Shading Conditions - Germán Álvarez-Tey; José Antonio Clavijo-Blanco; Álvaro Gil-García; Rafael Jiménez-Castañeda; Carmen García-López (Applied Sciences, 2019)
The shadow effect caused by nearby objects or the lack of cleaning significantly affects the performance of photovoltaics (PV) installations. This article analyses the bypass diode electrical behaviour and the thermal response of a PV crystalline module under shading or soiling conditions. PV cells of different substrings were covered progressively to simulate the effect of shading or soiling while a programmable electronic DC load was connected to a PV module to set an operating voltage. Three different tests were made to different PV crystalline technology. The paper characterizes in real conditions the I−V curve, bypass diode current, and front and back side PV cell temperature with contact sensor and infrared (IR) thermography, respectively. The results showed that the operation voltage established in the PV module defines the electrical bypass diode current and thermal response under normal operating conditions, shading or soiling. To show the bypass diode behaviour in such conditions, I−V curves were obtained, pointing out the value of the current that flows through bypass diodes in the whole voltage range.